Experience of outpatient follow-up of heart transplant recipients at Shumakov center - I. I. Muminov; N. N. Koloskova; V. N. Poptsov; V. M. Zakharevich; N. P. Mozheiko; S. A. Sakhovsky; A. O. Shevchenko (Вестник трансплантологии и искусственных органов, 2023)
Heart transplantation (HT) is considered the optimal therapy for end-stage heart failure. In recent years, the number of operations performed has been growing, which has led to a rise in the number of heart transplant recipients requiring outpatient follow-up.Objective: to evaluate the effectiveness of the model of dual personalized follow-up of heart transplant recipients in the consultative and diagnostic department of Shumakov National Medical Research Center of Transplantology and Artificial Organs.Materials and methods. The study included 1,436 patients under outpatient follow-up from January 2008 to December 2022. Recipient data, results of laboratory and instrumental examination methods, nature and frequency of complications at different follow-up periods were analyzed.Results: At the time of discharge from the hospital, 98.7% of patients had received triple-drug immunosuppressive therapy; 6 months later, methylprednisolone was discontinued in 72.2% of recipients. Mean tacrolimus level during the 1-year follow-up was 8.7 ± 2.7 ng/mL; in the period from 1 to 5 years of followup, the mean was 5.1 ± 2.4 ng/mL. At year 1 after transplantation, 23 (1.7%) recipients had been converted to everolimus; by the end of year 5 of follow-up, the number had increased to 8.6%. The most frequently detected complications during outpatient follow-up were: hypertension (48.65%), post-transplant diabetes mellitus (7.24%), nephropathy (35.97%), and malignant neoplasms (4.2%). Recipient survival, excluding in-hospital mortality, was 96.5%; and 88.0% at year 1 and 5 of follow-up, respectively.Conclusion: The dual personalized approach model for outpatient follow-up and treatment of heart transplant recipients will improve recipient survival and quality of life in the long-term post-HT period.